Mapping the Intellectual Structure of Knowledge Management Subject Area: A Co-citation Network Analysis - Zavaraqi, Rasoul (International journal of information science and management, 2016)
The aim of the research is mapping the intellectual structure of knowledge management subject area to explore more its past and present. This Scientometric research has been done by author co-citation analysis of KM during time span of 1990-2014. We also used new social network indicators to understand the field better. The findings showed that different specialties can be recognized in the KM field. Half of the specialties are interrelated which shows the interdisciplinary nature of the KM fields. The results also showed that the impact of works written by Davenport, Polanyi and Brown with 928, 650 and 513 citation is more than other core authors of the field, and the stability of Drucker, Schon, Nelson, and Polanyi Theories with 36, 29, 26 and 25 citation half-life is more than other theories.